2011
DOI: 10.1155/2011/317410
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Anesthetics during Thoracic Surgery

Abstract: Background. One-lung ventilation (OLV) during thoracic surgery may induce alveolar cell damage and release of proinflammatory mediators. The current trial was planned to evaluate effect of propofol versus isoflurane anesthesia on alveolar and systemic immune modulation during thoracic surgery. Methods. Fifty adult patients undergoing open thoracic surgery were randomly assigned to receive propofol (n = 25) or isoflurane (n = 25) anesthesia. The primary outcome measures included alveolar and plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…Mahmoud et al [27] found that alveolar and plasma concentrations of IL-8 and TNF-α were significantly lower in patients undergoing thoracic surgical procedures under 1 MAC isoflurane anesthesia compared to patients who received propofol (4 – 6 mg/kg/h)-based anesthesia [27]. Similarly, De Conno et al [28] investigated the modulatory effect of sevoflurane on inflammation in 54 patients undergoing thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoud et al [27] found that alveolar and plasma concentrations of IL-8 and TNF-α were significantly lower in patients undergoing thoracic surgical procedures under 1 MAC isoflurane anesthesia compared to patients who received propofol (4 – 6 mg/kg/h)-based anesthesia [27]. Similarly, De Conno et al [28] investigated the modulatory effect of sevoflurane on inflammation in 54 patients undergoing thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Influencing the functions of immunocompetent cells and inflammatory mediator gene expression and secretion, most anesthetics have a direct suppressive effect on cellular and neurohumoral immunity [ 7 ]. Every anesthetic has different immunosuppressive effects, and researchers generally agree that total intravenous anesthesia (TIVA) is less immunosuppressive than inhalational anesthesia [ 11 ]. Most commonly used in veterinary medicine, propofol also has shown immunosuppressive effects, but fewer than the other volatile anesthetics; moreover, it has some protective influences on the immune system.…”
mentioning
confidence: 99%
“…Volatile anesthetics have been shown to induce dose and time-dependent immune-modulatory effects (35). Desflurane and sevoflurane suppress local alveolar cytokine pro-inflammatory release in the ventilated lung after OLV, while propofol seems not to produce this advantageous effect (36). In particular, volatile anesthesia with desflurane attenuates the immune response and causes, as compared to propofol, a minor alveolar release of inflammatory mediators such as ICAM-1, polymorphonuclear (PMN) A elastase, IL-8 and IL-10 (37).…”
Section: Discussionmentioning
confidence: 99%